2018
DOI: 10.1109/jphot.2018.2883548
|View full text |Cite
|
Sign up to set email alerts
|

A New RAM Normalized 1$f$-WMS Technique for the Measurement of Gas Parameters in Harsh Environments and a Comparison With ${2f\!/\!1f}$

Abstract: A calibration-free first harmonic (1f) wavelength modulation spectroscopy (1f-WMS) technique for gas species parameter measurement is demonstrated. In this technique, the total magnitude of the 1f-WMS signal is normalized by a component of the 1f residual amplitude modulation signal. This method preserves the advantages of the traditional nf/1f-WMS (n ≥ 2) technique, such as the immunity to the non-absorbing systematic losses and the accurate recovery of gas parameters, without the requirement for non-absorbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Although the laser characterization process is not difficult by itself, the task of accurately tracking its variations in real time is nontrivial. More recently, Upadhyay et al have proposed a new calibration-free 2f -WMS technique to measure gas concentration and pressure without the need for laser pre-characterization [103][104][105][106]. Similar to the idea of DAS baseline fitting, the harmonic backgrounds, i.e., RAMs, are obtained by interpolating the non-absorbing wings of the X and Y components of the demodulated 1f, 2f, and 3f signals ( Figure 13).…”
Section: In Situ Parameter Fittingmentioning
confidence: 99%
“…Although the laser characterization process is not difficult by itself, the task of accurately tracking its variations in real time is nontrivial. More recently, Upadhyay et al have proposed a new calibration-free 2f -WMS technique to measure gas concentration and pressure without the need for laser pre-characterization [103][104][105][106]. Similar to the idea of DAS baseline fitting, the harmonic backgrounds, i.e., RAMs, are obtained by interpolating the non-absorbing wings of the X and Y components of the demodulated 1f, 2f, and 3f signals ( Figure 13).…”
Section: In Situ Parameter Fittingmentioning
confidence: 99%
“…In many cases, the RAM amplitude can be comparable to or even much larger than the absorption signal, which results in the absorption signal often drowning in the background and difficult to distinguish. The RAM also limits the [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Upadhyay et al demonstrated experimentally that the nonlinear gain of detectors varies with frequency and optical attenuation. During laser intensity fluctuations, the 2f /1f method will not be able to eliminate the nonlinear gain variation of the detector [7]. However, these problems can be well avoided if the same order harmonics are employed for normalization.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared absorption spectroscopy is widely researched due to numerous advantages including fast response, nonintrusive nature, and sensitive species-specific detection capabilities [1][2][3][4], compared with traditional gas-sensing techniques such as catalyst combustion [5][6][7], electrochemical [8][9][10], and semiconductor [11][12][13]. erefore, gas-sensing systems and sensors based on infrared absorption spectroscopy have been reported by many research groups in recent years, and many related techniques have been developed and improved to achieve high-sensitive sensing ability [14][15][16].…”
Section: Introductionmentioning
confidence: 99%